Introduction to Business Developmet of Teaching Materials With Business Planning - Saripuddin Hsb, S.E., M.Si, Jasman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Introduction to Business Developmet of Teaching Materials With Business Planning